Разработка транспортной складской системы на базе робота - Андрейко, Е. Р. (ХНУРЕ, 2021)
This work is devoted to development of Arduino-based MR hardware that will process information from coming from the environment using sensors and interacting with other network devices.
Keywords: роботы; транспортная складская система